Legal and economic determinants of restructuring processes in health care entities in Poland - Głód, Grzegorz; Langer, Maciej (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The majority of problems in the health care system originate in the limited financial resources, but the efficiency of the system is also — indirectly — affected by the management of these resources, which is sometimes not as effective as it might be. These problems become particularly apparent in the Polish public health care, undergoing constant reforms. This brings into focus the issue relating to restructuring processes, which are determined by relevant legal regulations and the competences of people in charge, who need to maintain the consistency of implementation. Aim: The article aims to analyse legal and economic determinants in the restructuring of health care entities in Poland, with particular emphasis on the possible application of restructuring proceedings to these entities. Further, it identifies key success factors for restructuring processes from the perspective of management. The following legal acts were included in the analysis: the Act of 15 May 2015 the Restructuring Law, the Act of 15 April 2011 on medical activity, the Act of 23 April 1964 the Civil Code, the Act of 28 February 2003 the Bankruptcy Law. The review of good management practices in the research area was presented. Results: Based on the analysis, recommendations concerning the implementation of restructuring processes in health care entities were formulated. The benefits stemming from the application of restructuring proceedings to health care entities were discussed. The key elements of the restructuring plan, accompanied with practical guidelines, were presented.